Numerical investigation and thermodynamic analysis of syngas production through chemical looping gasification using biomass as fuel. (15th June 2019) - Li, Zhenwei; Xu, Hongpeng; Yang, Wenming; Xu, Mingchen; Zhao, Feiyang
Highlights: Dynamic model is developed and well validated against biomass CLG experiments. Elevation of H2 yield is mainly due to partial oxidation and iron-steam reaction. Excessive steam accelerates the gasification of char and water-gas shift reaction. Oxygen carrier enhances the quality of syngas based on energy and exergy analyses. Abstract: Chemical looping gasification (CLG) is an innovative technology for the thermochemical conversion of biomass to produce high quality synthesis gas. In this study, a one-dimensional transient model considering partial oxidation of fuels and iron-steam reaction for biomass CLG fuel reactor was developed and validated against the experimental study utilizing Fe2 O3 as oxygen carrier (OC) and microalgae as fuel. The simulation results and the experimental data are in good agreement in terms of the detailed time-varying outlet gas species concentrations, gas yield, carbon conversion efficiency, and gasification efficiency. The effects of different operating temperature and steam flow on the gasification performance are also well predicted by the adopted reaction mechanisms. Energy and exergy analyses are applied to evaluate the energy sources based on the validated model, which demonstrates that the presence of OC can enhance both the quantity and quality of the valuable syngas.